Scandalizing the Goddess at Kodungallur - M. J. GENTES
The Cock Festival (or Minam Bharani Festival) at Sri Kurumba Kavu in central Kerala is known for the raucous, erotic, and insulting devotional practices of its participants. Thousands of devotees take part annually in the singing of highly explicit sexual songs and in the ceremonial pollution of the goddess Sri Kurumba's shrine. This festival is controversial but popular, and resembles in many ways descriptions of the ecstatic cults of the ancient Near East that spread throughout the Greco-Roman empire. Oracles of the goddess, called veiiccappitus (illuminators), reveal her wishes through trance and in their possessed state cut their foreheads with swords as they dance. The e~iccappitus, along with the atikajs, play major roles in the month-long, non-Brahminical Bharani Festival. Many Hindus find the treatment of the goddess during the festival reprehensible, while devotees feel she is pleased and sated by their amplification and celebration of her iakti (power). This paper presents firsthand descriptions of the temple and festival and discusses various ways of making sense of the activities of devotees.